2020
DOI: 10.1016/j.marchem.2020.103848
|View full text |Cite
|
Sign up to set email alerts
|

Dissolved organic matter dynamics in the pristine Krka River estuary (Croatia)

Abstract: In many estuarine systems, riverine discharge is the main source of dissolved organic matter (DOM). In contrast, karstic Krka River, with self-purifying ability, is characterized by very low DOM concentrations (~30 µM) and a diluting effect on DOM in the estuary. Interestingly, within the estuary a marked in-situ production is observed, particularly in summer. Pristine nature of the estuary makes it a natural laboratory to study the DOM dynamics, originated from 3 sources: the river the seawater and in-situ pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 81 publications
(101 reference statements)
2
22
0
Order By: Relevance
“…However, a similar increase is observed for all other components, showing a positive correlation with ΣL. Even though in situ production can also cause the increase of humic-like components ( Romera-Castillo et al, 2010 ; Marcinek et al, 2020 ), without additional biological information we cannot conclude that the correlation between ΣL and the DCu in late summer is related to any extent to a biological response to Cu-stress.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…However, a similar increase is observed for all other components, showing a positive correlation with ΣL. Even though in situ production can also cause the increase of humic-like components ( Romera-Castillo et al, 2010 ; Marcinek et al, 2020 ), without additional biological information we cannot conclude that the correlation between ΣL and the DCu in late summer is related to any extent to a biological response to Cu-stress.…”
Section: Resultsmentioning
confidence: 90%
“…Absorbance at 254 nm ( A 254 ) was expressed as the absorption coefficient ( a 254 ) in m −1 ( Stedmon and Nelson, 2015 ). The specific UV absorbance at 254 nm (SUVA 254 ) was calculated by dividing the absorption coefficient at 254 nm by the DOC concentration (m 2 g −1 C) and used as an indicator of the percentage of CDOM in the total DOM pool ( Marcinek et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Halocline is usually positioned between 1.5 and 3 m, with the thickness of the halocline layer varying between a few cm up to 1 m [ 12 , 54 ]. Special characteristics make this sampling location ideal for evaluating the mobility and fate of trace metals and natural organic matter [ 12 , 53 , 55 , 56 , 57 ]. Trace metals have been previously studied, although mainly in reference to their total concentrations [ 12 , 51 ].…”
Section: Methodsmentioning
confidence: 99%
“…In addition, some of the recent studies on sediments of the Krka River estuary showed detectable anthropogenic input (due to the nautical tourism) in local restricted areas, although the estuary generally is not considered polluted [51,52,58]. The sampling sites were selected to represent typical estuarine zones of varying anthropogenic input, physico-chemical gradients and biological activity [57,59]. Sampling was conducted on November 2019 and January of 2020 at three different locations along the Krka River estuary (Figure 7): Skradin bridge (denoted as SB), Martinska (denoted as MA) and Vrnaža port (denoted as VP), as well as two end-member locations: the Krka River water above the Skradinski Buk waterfalls (E1) and coastal seawater (E2).…”
Section: Study Sitementioning
confidence: 99%